The 2014 DAF survey at the University of Sheffield - Cox, Andrew; Williamson, Laurian (University of Edinburgh, 2015)
The Data Asset Framework methodology has evolved to provide a model for institutional surveys of researchers’ data practices and attitudes. At least 13 such studies have been published in the UK and internationally. The aim of this paper is to analyse the results from the 2014 DAF survey at the University of Sheffield and to reflect on the comparability of this with previous published studies. Comparison of the Sheffield results with those of other institutions is difficult particularly because of the divergence of questions asked in the different studies. Nevertheless, in terms of data practices and identifying training priorities there are common patterns.